Validity of wireless device measuring velocity of resistance exercises - Sato, K.; Beckham, G. K.; Carroll, K.; Bazyler, C.; Sha, Z.; Haff, G. (Journal of Trainology, 2015)
he purpose of the study was to identify the level of accuracy in velocity measurement from a newly developed inertia sensor. Design and Methods: Five subjects performed two dumbbell exercises for total of four sets of ten repetitions with a light intensity. Velocity data were taken and considered for analysis from two devices; the inertia sensor, wirelessly connected via Bluetooth™ to a smartphone, and a motion capture system. Both data were taken at the sampling frequency of 200 Hz. Identical data sets of peak and average velocity were analyzed with Pearson product-moment zero-order correlation using total 200 data points (5 subjects, 4 sets, and 10 repetitions) on both exercises with p value of 0.05. Data were also analyzed using the same statistical procedure for left and right side to ensure the device-device data consistency. Results: Results showed high correlations in both exercises between the two velocity measurement methods (0.80 - 0.92), indicating the accuracy of the data from the inertia sensor is supportive. Left and right side correlations were also high from the inertia sensor (0.90 - 0.93) indicating that the data were similar with relatively identical movements between the two limbs. Conclusions: With the accuracy of the velocity measurement, this would potentially replace currently used, wired devices to accommodate user-friendly, accessible to more exercises to measure velocity.